STEREOTACTIC BRAIN BIOPSY: A REVIEW OF 15 CASES WITH OUTCOMES - KUMAR, ASHOK; AS, CARVALHO; SURENDER; TJ, RAPPAI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Despite improvements in the imaging techniques which aid pre-operative diagnosis, starting specific treatment requires confirmation by histopathological examination (HPE). However dilemma arises in deep seated lesions, lesions in eloquent areas, and lesion in a patient with a poor performance score for palliation/adjuvant therapy. The aim of this study is to determine the diagnostic accuracy and benefits of stereotactic biopsy (STB) in cases of clinical dilemma plus its effect on post-operative stay, morbidity and mortality, and overall management of patients. Methods: In this study, a prospective analysis of 15 patients who underwent STB in our hospital from September 2019 to July 2020 was made. The histopathological data derived from the STB, its clinical benefits, and post-operative hospital stay were analyzed. Results: In terms of histopathology, glial tumor (66.7%) was the most common lesion. The success of obtaining positive STB samples in our study was 100%. Average post-operative stay was 3 days. The clinical benefits were immense as seen in the varied presentations and clinical dilemma with which the patients presented and a how a safely sourced tissue for histopathological diagnosis by STB greatly altered the treatment of the patient. Conclusion: STB is a multifaceted tool in clinical practice. It can be used in diagnostic and therapeutic situations. Furthermore, in recurrent high-grade cases, it aids in providing HPE diagnosis for a more logical adjuvant treatment than one that follows an assumed diagnosis based on image findings/undergo a high-risk interventional procedure to get a specimen. It is a relatively safe procedure.